The just energy transition partnership in South Africa: Identification and assessment of key factors driving international cooperation - Heiner von Lüpke (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
This paper investigates the implications of implementing the Just Energy Transition Partnership (JETP) in South Africa by exploring the factors that are at work when donors and recipients interact with each other. It analyses the JETP using global cooperation theories on climate change and identify mutual trust, based on shared norms; and process legitimacy via institutionalisation as the factors which can promote cooperation between donors and recipients. The paper contributes to the literature on international climate finance by providing novel insights through the analysis of the South African JETP as a single case study. It shows that the JETP is in fact a transnational policy process that needs to be institutionalised and legitimised to improve shortcomings of established conditionality instruments. The results might also inform the design of a climate club as proposed by the G7 as the JETPs are referred to as a possible instrument to cooperate with emerging economies.
Keywords: O13; O19; Q54; H87; 330; Just energy transition partnerships; International climate finance; International climate cooperation; South Africa